External and internal load variations in professional male cyclists during a 14-day training camp - Martinez-Gonzalez, B.; Vicini, M.; Giorgi, A. (Journal of Science and Cycling, 2024)
Professional athletes take part in training camps during specified periods of a season aiming to optimize training adaptations and in preparation for competitions. To improve performance and avoid overtraining it is crucial to find the right balance between training and rest. However, an intensified training period may result in overreaching. This study investigates internal and external training load parameters among 26 male professional cyclists during a 14-day training camp. Various metrics, including average power, distance, duration, fatigue, session-RPE, and training load, were measured and compared between the first and the second phase of the training camp. The second part showed increased values for these parameters, indicating heightened training intensity. Interestingly, sleep improved during the latter phase, and overall wellbeing remained unaffected. These findings may contribute to the field of professional cycling with valuable insights into the multifaceted aspect of athletes` performance and wellbeing during a training camp.